UNESCO "Training the Trainers in Information Literacy Workshop": Announcement and Call for Participants - Editorial Team (Evidence Based Library and Information Practice, 2008)
Welcome to the 11th European Conference of Medical and Health Libraries. Towards a new information space: innovations and renovations, Helsinki, Finland, 23rd - 28th June 2008. The Finnish Medical Library Association, Bibliothecarii Medicinae Fenniae (BMF), in collaboration with the National Library of Health Sciences, has the great honour and joy of inviting you to the 11th EAHIL (European Association for Health Information and Libraries) Conference. The EAHIL 2008 Helsinki conference offers a high quality scientific program. The proceedings will cover many interesting and current themes, especially the following topics inspired the authors: virtual communities and virtual libraries, evidence-based practice, education and professional development and new technologies and applications. In addition, a number of inspirational continuing education courses will be offered. Registration deadline for early birds: March 31, 2008 (380 €) Registration: April 1, 2008 onwards (430 €) Accompanying person: 230 € Continuing Education Courses: 60 € - 80 € Registration: http://www.congreszon.fi/eahil_2008/registration/ Please visit the EAHIL 2008 Helsinki home page http://www.congreszon.fi/eahil_2008/ for information. For current discussions about the conference, please visit the EAHIL 2008 Helsinki blog at http://eahil2008.blogspot.com/.